Analisis Komparatif Sistem Hukum Adat dan Hukum Positif dalam Harmonisasi Kebijakan Publik di Indonesia - Dina Rahmita; Muthi'ah Muthi'ah; Iqbal Hardiansyah; Wahyu Setiawan Rambe; Muhammad Alfarizi Lubis (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study examines the comparative analysis of customary law and positive law in the context of harmonizing public policy in Indonesia. The main objective is to explore the characteristics of each legal system and their interaction in the formulation of inclusive policies. Customary law, rooted in traditional norms, plays a significant role at the local level, while positive law focuses on formal regulations applied at the national level. Through literature review and analysis, this research identifies key aspects of both legal systems and their contributions to the harmonization of public policy. The findings indicate that the integration of customary law and positive law can strengthen fair and inclusive policies at various levels of governance.